A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species - Haran, Julien; Schütte, André; Friedman, Ariel-Leib-Leonid (Zootaxa, 2017)
The species of the genus Smicronyx sensu lato (Curculionidae, Curculioninae) occurring in Israel are reviewed. A total of seven species is recorded. Two species are newly recorded for the country (S. pauperculus Wollaston, 1864 and S. albosquamosus Wollaston, 1854), and two new species are described: S. jordanicus Haran and S. longitarsis Haran. A key to species, diagnosis of the new species, new biological and distribution data together with line illustrations of some characters, including male genitalia, and colour photographs of the habitus are provided.